The Need for Peace Education for University Students in Lebanon - Chehimi, Ghada; Joudi, Nadine (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Lebanon’s young generations face the harshest outcomes of the country’s continuous state of turmoil and instability. Regardless of their distinct social, economic and educational backgrounds, Lebanese youth seem to be victims of the aggressive politics, degenerative culture and misleading notions of what it means to be a peaceful individual. These conditions, though over-simplified, tend to necessitate a more institutionalized approach in directing youth and equipping them with peace education. This paper aims to explore the need for peace education for university students in Lebanon. It also investigates the extent to which a sample of Lebanese students and instructors are aware of the presence of the peace concept, and its method of application to the education environment. It also examines the shortcomings of current university students’ peace education, and recommends some major changes that need to be introduced to their curricula. Data is collected using a survey administered to 119 students from a variety of Lebanese universities, in addition to focus group discussions with 14 university professors. Research outcomes serve as a foundation for further research, application and or implementation of peace education in the curriculum of Lebanese universities.